PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL MARKOWITZ - Setyawati, Ni Putu Eka Cahya; Sudiartha, Gede Merta (E-Jurnal Manajemen, 2019)
Investment can be related to investing some funds in financial assets or real assets such as land, gold, shares, deposits, bonds and other forms. As a party who is make an investment, investors will be faced with a variety of options in investing that has a rate of return and risk-appropriate expectations. The ways that usually used by investors is to diversify through the creation of a portfolio. The aim of this research  is to know the stocks that can  be inserted into the optimal portofolio as well as the proportions of each of the stocks, that the model established by Markowitz. This research was conducted on the IDX30 index from January 2017 to January 2018, especially in the mining sector and consumer goods. The results showed, from 14 stock, 7 stock was selected as candidate of portfolio optimal Markowitz models. Stocks that are worth being a member of the optimal portfolio by a proportion of the allocation of each fund i.e. stocks ADRO (0.55%), ASII (0.15%), GGRM (17.61%), ICBP (9.46%), MEDC (5.275), UNVR (41.11%), and UNTR (25.86%), it gives the expected portfolio return of 3.2% and with the level of risk of 3.3%. Keywords: optimal portfolio, Markowitz model, mining sector and consumer goods